Integration Starts on Day One in Global Software Development Projects - Gotel, O.; Kulkarni, V.; Scharff, C.; Neak, L. (2008 IEEE International Conference on Global Software Engineering, 2008)
Since 2005, Pace University, Delhi University and the Institute of Technology of Cambodia have been partnering to offer students the opportunity to work on globally distributed software development projects. The innovative collaborative model has evolved towards an emphasis on technology mashups for development and communication, mentoring and auditing for assuring quality, and team and software integration for right-sourcing. This paper describes a project where students working in sub-teams were required to integrate their sub-components as a single system for a Cambodian environment. Furthermore, a well-defined design sub-component was subject to a competitive bidding process in an attempt to enhance quality though design diversity. The paper reports on our findings and summarizes the dos and don'ts associated with integration. Both team and software integration needs careful attention from day one on a project, a finding that has repercussions for educational and industrial practice.